STRATEGI PENANGANAN STUNTING DI KABUPATEN JENEPONTO - Sri Devi; Basri Bado; Citra Ayni Kamaruddin; Irwandi; Sri Astuty (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2025)
The problem of stunting in Indonesia, especially in Jeneponto Regency, is a major challenge that affects the quality of human resources (HR). This study aims to identify internal and external environmental conditions that affect the prevalence of stunting in Jeneponto Regency, as well as to formulate and determine priority strategies in local government efforts to reduce stunting rates. This type of research is quantitative descriptive, with a population of 383 people. The research sample consisted of 80 randomly selected respondents, as well as 7 expert respondents who had in-depth knowledge of stunting issues in the area. The data analysis technique used was SWOT analysis to identify strengths, weaknesses, opportunities, and threats, as well as the Analytic Hierarchy Process (AHP) method with the help of the Expert Choice application to determine the most appropriate and relevant priority strategies. The results of the study showed that the local government's strategy in reducing the prevalence of stunting was in Quadrant I (Growth-Oriented Strategy). These results indicate that the stunting reduction program is in a fairly advantageous position by utilizing internal strengths as basic capital and available external opportunities. The alternative strategic priorities produced are community empowerment through education on the use of PKH assistance and other social assistance, as well as combining stunting reduction programs with family welfare improvement programs through economic empowerment, nutritious food processing training, and increasing access to easily accessible health facilities